Adolescent Anxiety and Motivation in Seeking Entertainment During the Covid-19 Pandemic - Nurlaela Hamidah; Rizka Amalia Putri (Psycho Holistic, 2021)
Abstrak SSince the beginning of March 2020 the Covid 19 virus began to spread widely in Indonesia after previously spreading widely from the beginning of its spread in China then its spread to several European and Asian countries. The condition of the spread of the Covid 19 virus which was so quickly responded to by the government quite swiftly and responsively where the government made various policies to deal with and overcome the Covid 19 pandemic. With the government policies that have been put in place related to the spread of the Covid 19 Virus, people just stay at home because all work and educational activities are carried out at home due to the emergence of the implementation of work from home and study from home. Limitations to interact with each other directly, face to face and meet physically make humans have a fairly low level of communication and mobility of activities where they are conditioned to do their respective jobs without meeting with fellow individuals,even to communicate briefly even now feels very difficult to do directly. These conditions encourage the emergence of feelings of loneliness and boredom by individuals, especially adolescents. In general psychological concepts, there is a theory that explains that individual motivation is related to the emotions they feel. Because basically individuals do something because of the feelings that they feel and provide a stimulus to act according to their mindset. In relation to the problems discussed in this article, the motivation of adolescents to seek entertainment is influenced by emotions in the form of anxiety, boredom, and loneliness that they feel so that they feel they need to transfer these emotions as a form of self-control. This article aims to analyze the relevance of the theory of motivation and emotion to adolescent behavior during the pandemic, namely seeking entertainment for the anxiety they feel. The research method uses qualitative methods with library research.